Study of Arrival and Withdrawal of Southwest Summer Monsoon over Bangladesh and Analysis of Extreme Early and Late Arrival Events Using RegCM (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
This research attempts to identify the dates of arrival and withdrawal for the southwest summer monsoon over Bangladesh using observed data. In addition, both the extremely early and late arrival of summer monsoon are studied using the RegCM. - Rainfall, wind direction, wind speed, maximum temperature, minimum temperature, and relative humidity of 11 stations in Bangladesh for the months of May to October, for the years between 1990 to 2019, have been analyzed statistically. Secondly, two anomaly events were simulated using the Regional Climate Model (RegCM). This analysis is done for determining various spatial and temporal patterns during the arrival and withdrawal dates for the summer monsoon. It is found from this research that the arrival of the summer monsoon in the extreme southeastern region of the country is around 10 June. After covering the entire country by just 14 days, the summer monsoon completes its journey from Teknaf to the northwestern tip of the country via Sylhet. The summer monsoon begins to depart from extreme north-western Bangladesh on 4 October. It takes about 16 days to complete the withdrawal from Bangladesh via the southeastern route, with the average date being 20 October. Both the arrival and withdrawal dates have standard deviations ranging from 7 to 8 days and 5 to 7 days respectively. From the analysis of 30 years of data, the summer monsoon season lasts from 102 to 132 days.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(2), 2022, P 101-112